Method for improving high-cycle fatigue performance of Ti6Al4V titanium alloy

Through the combination of shot peening and femtosecond laser impact enhancement, the problem of insufficient high-period fatigue performance of Ti6Al4V titanium alloy is solved, and the material's significant performance improvement and fatigue life extension are achieved.

CN119571233APending Publication Date: 2025-03-07XIAN LASER TRANSMISSION TECH CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411911987.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Ti6Al4V titanium alloy fan blades are prone to local peeling, cracks and even fractures under complex working conditions, resulting in insufficient high-period fatigue performance and affecting the reliability of long-term service.

Method used

Using a combination of shot peening and femtosecond laser impact strengthening, a high-amplitude residual compressive stress and plastic deformation layer is introduced through shot peening, femtosecond laser impact removes surface defects and refines the grain structure, and optimizes the microstructure and surface integrity of the material.

Benefits of technology

It significantly improves the high-period fatigue performance of Ti6Al4V titanium alloy, extends the fatigue life, and enhances the crack resistance and toughness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571233A_ABST
    Figure CN119571233A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the high-cycle fatigue performance of a Ti6Al4V titanium alloy, and belongs to the technical field of metal material processing, and the method comprises the following steps: S1, determining shot peening strengthening parameters based on material performance parameters and related standards; according to the method, high-amplitude residual compressive stress is introduced through shot peening strengthening, the stress state of the surface and the depth direction of the material is changed, accordingly, crack extension can be restrained, the fatigue life is prolonged, in addition, a plastic deformation layer is induced to be generated under the surface depth in the shot peening process, the microstructure of the material is improved, and the anti-fatigue performance of the material is improved; through femtosecond laser shock, surface defects can be effectively removed, the surface compactness can be improved, microcracks can be reduced, and a refined grain structure can be generated, so that the strength and toughness of the material are further enhanced, the high-cycle fatigue performance of the material is further improved, the two are combined, the residual stress state is optimized, and the surface integrity is improved. The fatigue performance of the Ti6Al4V titanium alloy is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material processing, and in particular relates to a method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy. Background Art

[0002] The titanium alloy fan blades in high bypass ratio turbofan engines have long been widely used due to their excellent strength and impact resistance. However, in actual service, the fan blades are directly exposed to the natural atmosphere and are subjected to a variety of complex working conditions such as high-speed aerodynamic loads, fatigue accumulation, and foreign object impact. In particular, the titanium alloy part of the leading edge of the blade is extremely susceptible to impacts from foreign objects such as bird strikes. In addition, the leading edge stiffness and fatigue reserve of the blade are insufficient, and the leading edge of the blade is prone to local peeling, cracking, or even breakage. Therefore, the design needs to be further strengthened to improve its long-term service reliability under complex working conditions.

[0003] Aiming at the high-cycle fatigue performance of Ti6Al4V titanium alloy, in order to ensure its long life and high reliability in service, domestic and foreign countries have successively adopted and developed surface impact strengthening methods such as shot peening, laser, and ultrasound to construct a fatigue-resistant surface metamorphic layer, so that it has an ultra-fine grain surface microstructure and an ultra-high residual compressive stress field, so as to improve its resistance to stress cracking and fatigue fracture, and realize fatigue-resistant manufacturing. However, a single strengthening method still has limitations in achieving a one-step improvement in the surface integrity and fatigue performance of components, thereby reducing the surface integrity of Ti6Al4V titanium alloy after strengthening.

[0004] In order to avoid the above technical problems, it is necessary to provide a method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy to overcome the above defects in the prior art. Summary of the invention

[0005] The object of the present invention is to provide a method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy, comprising the following steps:

[0007] S1. Determine shot peening parameters based on material performance parameters and relevant standards;

[0008] S2. Determine the femtosecond laser shock peening parameters:

[0009] S3, post-processing by shot peening and femtosecond laser shock peening;

[0010] S4. Conduct high cycle fatigue performance assessment on fatigue specimens after composite strengthening;

[0011] S5. Characterization of fracture morphology before and after strengthening and study of strengthening mechanism.

[0012] As a preferred implementation scheme, the shot peening parameters are determined by using the HB / Z26-2011 aviation parts shot peening process to determine the shot peening related process parameters, and the shot peening related process parameters include shot medium, shot strength, shot peening angle, shot peening pressure and shot peening time.

[0013] As a preferred embodiment, the shot medium is AISI 1075, the shot strength is 700-900 MPa, the shot peening angle is 60° or 90°, the shot peening pressure is 0.2-0.8 MPa, and the shot peening time is 10-20 s.

[0014] As a preferred embodiment, the femtosecond laser shock strengthening parameters are determined by using different wavelengths of femtosecond pulse lasers to strengthen the Ti6Al4V titanium alloy. A high-wavelength femtosecond laser with a wavelength of 1030 nm is selected to strengthen the Ti6Al4V titanium alloy. The ablation threshold is 0.2 J / cm 2 .

[0015] As a preferred embodiment, the femtosecond laser shock peening parameters include laser energy, repetition frequency, spot diameter, pulse width, overlap rate and number of impacts, the laser energy is 150μJ, the repetition frequency is 20KHz, the spot diameter is 30μm, the pulse width is 290fs, the overlap rate is 50%, and the number of impacts is 1 time.

[0016] As a preferred embodiment, the shot peening comprises the following steps:

[0017] S1. After selecting the appropriate shot peening medium (AISI 1075), set the air pressure, spray angle and particle size of the shot peening equipment according to the material properties and experimental requirements;

[0018] S2. Adjust the parameters of shot peening pressure, shot peening time and shot peening angle at the shot peening equipment control end;

[0019] S3, placing the sample in the shot peening equipment and performing shot peening according to the set parameters;

[0020] S4. After shot peening, remove the residue on the surface and clean it with an ultrasonic cleaner.

[0021] As a preferred embodiment, the femtosecond laser shock peening comprises the following steps:

[0022] S1. Based on the surface state after shot peening, the parameters of the femtosecond laser system, such as pulse energy, pulse width, spot size and repetition frequency, are set through the femtosecond laser control terminal;

[0023] S2, placing the fatigue specimen on the five-axis machining platform of the femtosecond laser strengthening equipment, and adjusting the beam focal length and scanning path based on the thickness of the fatigue specimen;

[0024] S3, start the laser to perform scanning processing.

[0025] As a preferred embodiment, the high cycle fatigue performance assessment of the composite strengthened fatigue specimen comprises the following steps:

[0026] S1. Select the specimens that have been shot peened and femtosecond laser shock strengthened and whose size and shape meet the standard specimen specifications, and perform the final cleaning on the specimens to remove any residual oil or impurities;

[0027] S2. Check whether the power supply, control system and mechanical components of the fatigue machine equipment are normal to ensure safe operation;

[0028] S3. Perform necessary calibration, including calibration of load sensors and displacement sensors, to ensure the accuracy of test data;

[0029] S4. Fix the specimen in the fixture of the testing machine to ensure uniform clamping, no slippage, and no additional stress concentration;

[0030] S5. Input static load, dynamic load and frequency step by step at the fatigue machine control end, start the QBG-100 fatigue test machine, and monitor the load, displacement and strain in real time during the test to ensure that all parameters are within the set range;

[0031] S6. When fatigue fracture occurs on the specimen, the number of cycles and stress amplitude at the time of fracture shall be recorded immediately.

[0032] As a preferred embodiment, the fracture morphology characterization before and after strengthening and the strengthening mechanism research include the following steps:

[0033] S1. Select the specimens that broke after fatigue testing, including unreinforced and composite-reinforced specimens;

[0034] S2. Use wire cutting equipment to cut the fatigue part into specimens of appropriate size:

[0035] S3. Use a scanning electron microscope (SEM) to observe the fracture morphology. After placing the sample on the stage in the chamber, close the chamber door, evacuate the chamber, turn on the electron gun, set the acceleration voltage to 5-20 kV, and adjust the focal length to obtain a clear fracture microscopic morphology.

[0036] S4. Through segmented observation and mechanical property data, the fatigue crack initiation location and characteristics before and after strengthening are analyzed, and the specific mechanisms of how shot peening and femtosecond laser shock strengthening inhibit crack initiation, slow crack propagation and enhance fatigue performance are explained.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The present invention introduces high-amplitude residual compressive stress through shot peening, changes the stress state of the material surface and depth direction, increases the difficulty of fatigue crack initiation, thereby inhibiting crack expansion and extending fatigue life. In addition, the shot peening process induces a plastic deformation layer below the surface depth, improves the microstructure of the material, and enhances its fatigue resistance. The surface defects can be effectively removed through femtosecond laser impact, the surface density can be increased, the presence of microcracks can be reduced, and a refined grain structure can be generated at the same time. The strength and toughness of the material are further enhanced, and its high-cycle fatigue performance is improved. The combination of the two achieves a significant improvement in the fatigue performance of the Ti6Al4V titanium alloy by optimizing the residual stress state and improving the surface integrity.

[0039] The present invention determines the shot peening process and parameters through HB / Z26-2011, and can introduce high-amplitude residual compressive stress through shot peening. The residual compressive stress changes the stress state of the material surface and in the depth direction, increases the difficulty of fatigue crack initiation, can effectively resist external tensile stress, delay the generation and expansion of cracks, and thus prolong fatigue life. The shot peening process induces a plastic deformation layer at a depth below the surface layer, refines the grains of the material, and increases the dislocation density. The change in the microstructure enhances the surface hardness and crack resistance, and improves the resistance of the surface layer to fatigue crack initiation. The refined grain structure also increases the number of grain boundaries, further hinders the expansion of cracks, and effectively delays the formation of fatigue cracks.

[0040] The present invention performs strengthening by determining appropriate femtosecond laser shock strengthening related parameters. Femtosecond laser shock strengthening mainly improves the integrity of the material surface through the instantaneous ultra-high temperature and ultra-high pressure brought by laser pulses. It can effectively remove surface defects, improve surface density, reduce the existence of microcracks, and produce a refined grain structure. This refined microstructure further enhances the strength and toughness of the material, thereby improving its high-cycle fatigue performance. Femtosecond laser shock strengthening is performed on the basis of shot peening strengthening, which can further optimize the residual stress distribution on the material surface. By generating a shallow and relatively uniformly distributed residual compressive stress layer on the surface of the material, it helps to effectively offset the tensile stress introduced by the external alternating load, further prevent the expansion of cracks, and improve fatigue resistance.

[0041] The present invention uses a QBG-100 high-frequency fatigue testing machine to perform high-cycle fatigue performance assessment on the test pieces before and after strengthening. Through reasonable testing methods such as step-by-step loading, the method can accurately evaluate the improvement effect of the method on the high-cycle fatigue performance of Ti6Al4V titanium alloy, providing reliable data support for verifying the effectiveness of the method and optimizing the process. The microstructure evolution of the fracture morphology of the fatigue-failed component is characterized by using a microscope, and the strengthening mechanism of the composite strengthening treatment for improving the high-cycle fatigue performance of the Ti6Al4V titanium alloy is explained. By analyzing the fracture morphology observation and mechanical property data, the fatigue crack initiation position and characteristics before and after strengthening can be deeply understood, as well as how shot peening and femtosecond laser shock strengthening inhibit crack initiation, slow down crack propagation and enhance fatigue performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a schematic diagram of the overall process of the method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy according to the present invention;

[0043] Figure 2 The present invention is a schematic diagram of the mechanism of shot peening and composite femtosecond laser shock strengthening;

[0044] Figure 3 This is a schematic diagram of the surface residual stress distribution after shot peening + strengthening with different femtosecond laser energies in the present invention;

[0045] Figure 4 The present invention is a comparison of fatigue limits before and after composite strengthening;

[0046] Figure 5 This is a schematic diagram of the fracture morphology of a fatigue failure specimen before and after composite strengthening according to the present invention. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with the embodiments.

[0048] The following examples are used to illustrate the present invention, but they cannot be used to limit the scope of protection of the present invention. The conditions in the examples can be further adjusted according to specific conditions. Simple improvements to the method of the present invention under the premise of the concept of the present invention belong to the scope of protection claimed in the present invention.

[0049] See also Figure 1-5 The present invention provides a method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy, comprising the following steps:

[0050] S1. Determine shot peening parameters based on material performance parameters and relevant standards;

[0051] S2. Determine the femtosecond laser shock peening parameters:

[0052] S3, post-processing by shot peening and femtosecond laser shock peening;

[0053] S4. Conduct high cycle fatigue performance assessment on fatigue specimens after composite strengthening;

[0054] S5. Characterization of fracture morphology before and after strengthening and study of strengthening mechanism.

[0055] Shot peening can introduce high-amplitude residual compressive stress, change the stress state on the surface and in the depth direction of the material, increase the difficulty of fatigue crack initiation, thereby inhibiting crack expansion and extending fatigue life. In addition, the shot peening process induces a plastic deformation layer deep below the surface, improves the microstructure of the material, and enhances its fatigue resistance. Femtosecond laser shock can effectively remove surface defects, increase surface density, reduce the presence of microcracks, and produce a refined grain structure. This further enhances the strength and toughness of the material, thereby improving its high-cycle fatigue performance. The combination of the two, by optimizing the residual stress state and improving surface integrity, has achieved a significant improvement in the fatigue performance of Ti6Al4V titanium alloy.

[0056] The present invention provides an embodiment to determine shot peening parameters. The shot peening related process parameters are determined through the HB / Z26-2011 aviation parts shot peening process. The shot peening related process parameters include shot medium, shot strength, shot peening angle, shot peening pressure and shot peening time.

[0057] The present invention provides an embodiment, the shot medium is AISI 1075, the shot strength is 700-900 MPa, the shot peening angle is 60° or 90°, the shot peening pressure is 0.2-0.8 MPa, and the shot peening time is 10-20 s.

[0058] The present invention provides an embodiment to determine the femtosecond laser shock strengthening parameters, and the ablation threshold of Ti6Al4V titanium alloy is different by using femtosecond pulse lasers of different wavelengths. A high-wavelength femtosecond laser with a wavelength of 1030nm is selected to strengthen Ti6Al4V titanium alloy, and the ablation threshold is 0.2J / cm 2 .

[0059] The present invention provides an embodiment, in which the femtosecond laser shock strengthening parameters include laser energy, repetition frequency, spot diameter, pulse width, overlap rate and number of impacts, the laser energy is 150μJ, the repetition frequency is 20KHz, the spot diameter is 30μm, the pulse width is 290fs, the overlap rate is 50%, and the number of impacts is 1 time.

[0060] The shot peening process and parameters are determined by HB / Z26-2011. Shot peening can introduce high-amplitude residual compressive stress. This residual compressive stress changes the stress state of the material surface and in the depth direction, increases the difficulty of fatigue crack initiation, and can effectively resist external tensile stress, delay the generation and expansion of cracks, thereby extending fatigue life. The shot peening process induces a plastic deformation layer deep below the surface, which refines the grains of the material and increases the dislocation density. This change in microstructure enhances the surface hardness and crack resistance, and improves the surface's resistance to fatigue crack initiation. The refined grain structure also increases the number of grain boundaries, further hindering the expansion of cracks and effectively delaying the formation of fatigue cracks.

[0061] like Figure 2 and Figure 3 As shown, the present invention provides an embodiment for shot peening, comprising the following steps:

[0062] S1. After selecting the appropriate shot peening medium (AISI 1075), set the air pressure, spray angle and particle size of the shot peening equipment according to the material properties and experimental requirements;

[0063] S2. Adjust the parameters of shot peening pressure, shot peening time and shot peening angle at the shot peening equipment control end;

[0064] S3, placing the sample in the shot peening equipment and performing shot peening according to the set parameters;

[0065] S4. After shot peening, remove the residue on the surface and clean it with an ultrasonic cleaner.

[0066] The present invention provides an embodiment for performing femtosecond laser shock peening, comprising the following steps:

[0067] S1. Based on the surface state after shot peening, the parameters of the femtosecond laser system, such as pulse energy, pulse width, spot size and repetition frequency, are set through the femtosecond laser control terminal;

[0068] S2, placing the fatigue specimen on the five-axis machining platform of the femtosecond laser strengthening equipment, and adjusting the beam focal length and scanning path based on the thickness of the fatigue specimen;

[0069] S3, start the laser to perform scanning processing.

[0070] The neck area of ​​the fatigue specimen is first strengthened by shot peening. During the shot peening process, high-speed projectiles hit the surface of the material, causing severe plastic deformation of the surface layer, refining the grains of the material and increasing the dislocation density. This change in the microstructure enhances the surface hardness and crack resistance, and improves the surface layer's resistance to fatigue crack initiation. The refined grain structure also increases the number of grain boundaries, further hindering the propagation of cracks and effectively delaying the formation of fatigue cracks. At the same time, the high-amplitude residual compressive stress introduced by shot peening effectively offsets the tensile stress generated by the external load, delaying the initiation and early propagation of fatigue cracks. The shot strengthening post-treatment uses an extremely short pulse width to cause non-thermal equilibrium removal or micro-melting of the material under ultra-fast heating and cooling, thereby reducing the microscopic defects left after shot peening. This process can significantly reduce surface roughness, reduce the presence of microcracks and scratches, reduce the risk of crack initiation, and make the material surface more uniform and smooth, thereby delaying the early formation of fatigue cracks. At the same time, femtosecond laser shock can produce highly concentrated shock waves on the surface of the material, thereby introducing a shallow and relatively evenly distributed residual compressive stress layer, which helps to effectively offset the tensile stress introduced by external alternating loads, further prevent the expansion of cracks, and improve fatigue resistance.

[0071] After shot peening combined with femtosecond laser shock peening of different energies, compared with the untreated +5.07MPa tensile stress, after different composite strengthening processes, the tensile stress is converted into compressive stress, and the residual compressive stress reaches a maximum of -514MPa when the shot peening + femtosecond laser energy is 150μJ, with a large increase. It is believed that shot peening introduces a large amount of plastic deformation on the surface of the material through the impact of high-speed projectiles, inducing high-amplitude residual compressive stress. This process leads to grain refinement through the generation and movement of dislocations, enhancing the hardness and strength of the surface layer, thereby effectively increasing the compressive stress level of the surface layer. Secondly, femtosecond laser shock peening uses short-pulse high-energy lasers to produce strong transient thermal effects and shock waves on the surface of the material, further strengthening the compressive stress introduced by shot peening. In a very short time, the laser energy causes the surface material to instantly heat up and produce local melting, and the subsequent rapid cooling causes the material to return to a solid state, forming an additional compressive stress layer. The effect of the shock wave also deepens the distribution of compressive stress, forming a uniform and stable residual compressive stress field.

[0072] like Figure 4 As shown, the present invention provides an embodiment for performing high cycle fatigue performance assessment on a fatigue specimen after composite strengthening, comprising the following steps:

[0073] S1. Select the specimens that have been shot peened and femtosecond laser shock strengthened and whose size and shape meet the standard specimen specifications, and perform the final cleaning on the specimens to remove any residual oil or impurities;

[0074] S2. Check whether the power supply, control system and mechanical components of the fatigue machine equipment are normal to ensure safe operation;

[0075] S3. Perform necessary calibration, including calibration of load sensors and displacement sensors, to ensure the accuracy of test data;

[0076] S4. Fix the specimen in the fixture of the testing machine to ensure uniform clamping, no slippage, and no additional stress concentration;

[0077] S5. Input static load, dynamic load and frequency step by step at the fatigue machine control end, start the QBG-100 fatigue test machine, and monitor the load, displacement and strain in real time during the test to ensure that all parameters are within the set range;

[0078] S6. When fatigue fracture occurs on the specimen, the number of cycles and stress amplitude at the time of fracture shall be recorded immediately.

[0079] The high-cycle fatigue performance of fatigue specimens before and after strengthening was evaluated by using the step-by-step loading method. First, the fatigue specimens were tested at a lower stress level. At this stress level, fatigue fracture would not occur after 1×106 cyclic loading. After the first 1×106 cyclic loading was completed, the fatigue stress level was increased to the second step. The stress increase generally did not exceed 10% of the initial stress. The specimen was loaded step by step until fatigue fracture. For the fatigue specimens without strengthening treatment, the results showed that the average fatigue limit was 388.60MPa. Taking shot peening + 150μJ femtosecond laser as an example, the fatigue limit after composite strengthening was 446.21MPa, which was about 14.83% higher than that without strengthening treatment.

[0080] like Figure 5 As shown, the present invention provides an embodiment, the fracture morphology characterization before and after strengthening and the strengthening mechanism research, including the following steps:

[0081] S1. Select the specimens that broke after fatigue testing, including unreinforced and composite-reinforced specimens;

[0082] S2. Use wire cutting equipment to cut the fatigue part into specimens of appropriate size:

[0083] S3. Use a scanning electron microscope (SEM) to observe the fracture morphology. After placing the sample on the stage in the chamber, close the chamber door, evacuate the chamber, turn on the electron gun, set the acceleration voltage to 5-20 kV, and adjust the focal length to obtain a clear fracture microscopic morphology.

[0084] S4. Through segmented observation and mechanical property data, the fatigue crack initiation location and characteristics before and after strengthening are analyzed, and the specific mechanisms of how shot peening and femtosecond laser shock strengthening inhibit crack initiation, slow crack propagation and enhance fatigue performance are explained.

[0085] Shot peening + femtosecond laser shock peening introduces high-amplitude residual compressive stress and surface plastic deformation, so that the crack initiation position is transferred from the surface of the material to the inside of the material. This transfer effectively delays the formation of surface fatigue cracks. Fracture observation shows that the crack source position of the shot peened specimen is usually located in the sub-surface below the surface, indicating that the fatigue resistance of the material is significantly enhanced when subjected to alternating loads. The composite strengthening mechanism is as follows: Shot peening introduces surface plastic deformation and high-amplitude residual compressive stress through the impact of high-speed projectiles, forming a compressive stress layer, thereby effectively offsetting the external The tensile stress generated by the load delays the initiation and expansion of fatigue cracks. Secondly, femtosecond laser shock strengthening utilizes the transient thermal effect of short-pulse laser to optimize the microstructure of the material surface, reduce surface defects, improve the density and uniformity of the surface layer, and further enhance the fatigue strength. In addition, the micro melting and rapid cooling formed by femtosecond laser shock lead to grain refinement and increase the dislocation density, thereby improving the strength and toughness of the material. The synergistic effect of these two strengthening methods promotes the toughness and crack resistance of Ti6Al4V titanium alloy under fatigue load and significantly prolongs the fatigue life.

[0086] The working principle and use process of the present invention are as follows: First, a Ti6Al4V titanium alloy tensile high cycle fatigue specimen is selected, and the shot peening equipment, femtosecond laser, high frequency fatigue testing machine and related tools are checked to ensure normal operation. The shot peening strengthening is based on HB / Z 26-2011 to determine the parameters. The principle is that the shot medium hits the material surface under specific conditions, causing plastic deformation, introducing high-amplitude residual compressive stress, changing the stress state, increasing the difficulty of crack initiation, and delaying crack propagation. After selecting the medium, set the equipment parameters for shot peening. After completion, clean and wash. After the parameters are determined by femtosecond laser shock strengthening, based on its instantaneous ultra-high temperature and ultra-high pressure principles, the specimen is processed on a five-axis machining platform to remove defects, improve density, reduce cracks, refine grains, and optimize residual stress distribution. After cleaning, the qualified specimens after strengthening are selected, and the parameters are set on the fatigue testing machine and the data are monitored for performance assessment. Finally, the fracture of the fatigue-failed component is cut, cleaned, blown dry, and fixed. The parameters are set in a scanning electron microscope to observe the micromorphology and analyze the strengthening mechanism. The effects of shot peening and femtosecond laser shock strengthening on crack initiation, propagation and performance are explained through observation and mechanical property data. Shot peening inhibits cracks by introducing residual compressive stress and changing the microstructure, and femtosecond laser shock strengthening enhances material performance by improving surface integrity and optimizing residual stress distribution.

[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy, characterized in that: The following steps are involved: S1. Determine shot peening parameters based on material performance parameters and relevant standards; S2. Determine the femtosecond laser shock peening parameters: S3, post-processing by shot peening and femtosecond laser shock peening; S4. Conduct high cycle fatigue performance assessment on fatigue specimens after composite strengthening; S5. Characterization of fracture morphology before and after strengthening and study of strengthening mechanism.

2. The method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy according to claim 1, characterized in that: The shot peening parameters are determined by using the HB / Z26-2011 aviation parts shot peening process to determine the shot peening related process parameters, and the shot peening related process parameters include shot medium, shot strength, shot peening angle, shot peening pressure and shot peening time.

3. The method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy according to claim 2, characterized in that: The shot medium is AISI 1075, the shot strength is 700-900 MPa, the shot peening angle is 60° or 90°, the shot peening pressure is 0.2-0.8 MPa, and the shot peening time is 10-20 s.

4. The method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy according to claim 1, characterized in that: The femtosecond laser shock strengthening parameters are determined by using different wavelengths of femtosecond pulse lasers to strengthen the Ti6Al4V titanium alloy. A high-wavelength femtosecond laser with a wavelength of 1030 nm is selected to strengthen the Ti6Al4V titanium alloy. The ablation threshold is 0.2 J / cm 2 .

5. The method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy according to claim 1, characterized in that: The femtosecond laser shock peening parameters include laser energy, repetition frequency, spot diameter, pulse width, overlap rate and number of impacts. The laser energy is 150 μJ, the repetition frequency is 20 KHz, the spot diameter is 30 μm, the pulse width is 290 fs, the overlap rate is 50%, and the number of impacts is 1 time.

6. The method for improving the high cycle fatigue performance of Ti6Al4V titanium alloy according to claim 1, characterized in that: The shot peening process comprises the following steps: S1. After selecting the appropriate shot peening medium (AISI 1075), set the air pressure, spray angle and particle size of the shot peening equipment according to the material properties and experimental requirements; S2. Adjust the parameters of shot peening pressure, shot peening time and shot peening angle at the shot peening equipment control end; S3, placing the sample in the shot peening equipment and performing shot peening according to the set parameters; S4. After shot peening, remove the residue on the surface and clean it with an ultrasonic cleaner.

7. The method for improving high cycle fatigue performance of Ti6Al4V titanium alloy according to claim 1, characterized in that: The femtosecond laser shock peening comprises the following steps: S1. Based on the surface state after shot peening, the parameters of the pulse energy, pulse width, spot size and repetition frequency of the femtosecond laser system are set through the femtosecond laser control terminal; S2, placing the fatigue specimen on the five-axis machining platform of the femtosecond laser strengthening equipment, and adjusting the beam focal length and scanning path based on the thickness of the fatigue specimen; S3, start the laser to perform scanning processing.

8. The method for improving high cycle fatigue performance of Ti6Al4V titanium alloy according to claim 1, characterized in that: The high cycle fatigue performance assessment of the composite strengthened fatigue specimen comprises the following steps: S1. Select the specimens that have been shot peened and femtosecond laser shock strengthened and whose size and shape meet the standard specimen specifications, and perform the final cleaning on the specimens to remove any residual oil or impurities; S2. Check whether the power supply, control system and mechanical components of the fatigue machine equipment are normal to ensure safe operation; S3. Perform necessary calibration, including calibration of load sensors and displacement sensors, to ensure the accuracy of test data; S4. Fix the specimen in the fixture of the testing machine to ensure uniform clamping, no slippage, and no additional stress concentration; S5. Input static load, dynamic load and frequency step by step at the fatigue machine control end, start the QBG-100 fatigue test machine, and monitor the load, displacement and strain in real time during the test to ensure that all parameters are within the set range; S6. When fatigue fracture occurs on the specimen, the number of cycles and stress amplitude at the time of fracture shall be recorded immediately.

9. The method for improving high cycle fatigue performance of Ti6Al4V titanium alloy according to claim 7, characterized in that: The fracture morphology characterization before and after strengthening and the strengthening mechanism research include the following steps: S1. Select the specimens that broke after fatigue testing, including unreinforced and composite-reinforced specimens; S2. Use wire cutting equipment to cut the fatigue part into specimens of appropriate size: S3. Use a scanning electron microscope (SEM) to observe the fracture morphology. After placing the sample on the stage in the chamber, close the chamber door, evacuate the chamber, turn on the electron gun, set the acceleration voltage to 5-20 kV, and adjust the focal length to obtain a clear fracture microscopic morphology. S4. Through segmented observation and mechanical property data, the fatigue crack initiation location and characteristics before and after strengthening are analyzed, and the specific mechanisms of how shot peening and femtosecond laser shock strengthening inhibit crack initiation, slow crack propagation and enhance fatigue performance are explained.

Citation Information

Cited By

  • Turbine guide blade stress relief structure and preparation method thereof

    CN120667212A

  • Treatment process for improving three-point bending fatigue limit of thin-wall titanium alloy test piece

    CN120831289A

  • A method for improving high-cycle fatigue performance of TiAl alloy by shot peening

    CN122751114A

  • A method for improving high-temperature high-cycle fatigue performance of TiAl alloy through pre-oxidation

    CN122918478A